A dolphin is not a fish = un delfin no es un pez - Chessen, Betsey, 1970-; Chanko, Pamela, 1968- (New York : Scholastic, 2003)
Photographs and simple text describe some of the differences between dolphins and fish.
In English and Spanish.
Keywords: Dolphins -- Juvenile literature; Fishes -- Juvenile literature; Spanish language materials -- Bilingual